2006
DOI: 10.1007/s00198-005-0032-7
|View full text |Cite
|
Sign up to set email alerts
|

Community-dwelling seniors who present to the emergency department with a fall do not receive Guideline care and their fall risk profile worsens significantly: a 6-month prospective study

Abstract: We conclude that this group of community-dwelling fallers, who presented for ED care with a clinical profile suggesting a high risk of further falls and fracture, did not receive Guideline care and worsened in their fall risk profile by 29.5%. This gap in care, at least in one centre, suggests further investigation into alternative approaches to delivering Guideline standard health service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 65 publications
1
74
0
2
Order By: Relevance
“…Eighty percent of these injuries are secondary to a fall [2]. The majority, 65-79%, of these older patients are discharged home [3,4]. Unfortunately, even in community dwelling functionally independent older persons, minor trauma is a precursor to functional decline and ultimately diminished quality of life [2,5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighty percent of these injuries are secondary to a fall [2]. The majority, 65-79%, of these older patients are discharged home [3,4]. Unfortunately, even in community dwelling functionally independent older persons, minor trauma is a precursor to functional decline and ultimately diminished quality of life [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that most patients do not receive care consistent with guideline recommendations for the management of patients sustaining a fall [4,8]. Sirois et al found that the suboptimal ED care for independent injured seniors originates from the ED physicians' difficulty to discriminate between patients at risk of decline from those who are not [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ED biomarker assays are not useful in predicting 3-month functional decline or mobility impairments beyond what is predicted by frailty status alone in this population. Since emergency visits are reported as missed opportunities for interventions and since many seniors are discharged without receiving proper care [38,39] we believe that the use of quick and easy tools (such as the CSHA-CFS or SOF scales) seem more useful to help screen frail seniors who are at risk of functional or mobility impairment after an ED visit for a minor injury.…”
Section: Resultsmentioning
confidence: 99%
“…Guidelines alone are not sufficient; for example, a 2006 study in British Columbia determined that that <5% of older adults presenting to the emergency department (ED) with a fall received care consistent with the 2001 AGS/BGS guidelines. 9 Indeed, an important barrier to the implementation of Arnold and Gyurcsik's modified fall-prevention guidelines 1 will simply be getting the appropriate people with OA to the physiotherapist or community exercise provider for treatment. This is no small feat: another study, conducted in Ontario in 2009, determined that 62% of older adults presenting to the ED with a fall had no documented referral, and only 1.2% of those who did receive one were referred to physiotherapy.…”
mentioning
confidence: 99%